Bigmouth Strikes Again: The Controversies of Morrissey and Cancel Culture. (July 2022) - Pereira de Sá, Simone; Pereira Alberto, Thiago
On May 14, 2019, Morrissey performed on American television using a pin of the far right For Britain party. When criticized, he succinctly responded on Twitter: " Why don't you have freedom of speech? Or freedom to wear a pin on TV? " His online fandom reacted vehemently suggesting a "cancellation" of the artist. In this context, our proposal is to track constitutive parts of this process of "deception" with Morrissey, focusing specifically on a phenomenon that has gained visibility on socio-technical networks: the idea of "canceling." To gauge the reaction of his fandom, we address this event from the perception that this response to the singer took place on the horizon of expectations constructed through the experience that fans had with his career over the decades. We also use the notion of expressive coherence, as an analytical guide to understand some of the implications and tensions related to Morrissey's trajectory, examining how his historically constituted nostalgic performance tracks and sheds light on two questions that are essential to our analysis: "Was he really always like this?"; and "How did he become this person?" These are conjugated to a definitive affirmation: "I cannot be his fan anymore."